Une méthode de suivi de la vulnérabilité systémique à l’érosion et la submersion marines - Catherine Meur-Ferec; Iwan Le Berre; Lucie Cocquempot; Élisabeth Guillou; Alain Henaff; Thibaud Lami; Nicolas Le Dantec; Pauline Letortu; Manuelle Philippe; Camille Noûs (Développement Durable et Territoires)
Coastal development, combined with the intrinsic mobility of coasts and the context of climate change, tends to increase the vulnerability of coastal territories. This article proposes, on one hand, a renewed interdisciplinary approach to the concept of vulnerability allowing to overcome the nature/society dichotomy. On the other hand, the paper presents an inter-sectoral researchers-managers approach to build a series of indicators to monitor the four components of systemic vulnerability (hazards, stakes, management and representations). These indicators lay the ground for an integrated observatory, source of data for research as well as to inform decisions regarding the adaptation of coastal territories.